Differences in Function of the Urinary Tract Before and After Pelvic Floor Muscle Exercise (PFME) in Pregnant Women - Fari, Aniska Indah; Anggraini, Novita; Windahandayani, Veroneka Yosefha; Pranata, Lilik (Media Karya Kesehatan, 2024)
Physiological changes that occur during pregnancy affect the entire woman's body, especially the digestive, respiratory, cardiovascular, skin, hormonal, metabolic, musculoskeletal, breast, immune and reproductive systems, felt in the external and internal genital areas. Common symptoms during pregnancy include changes in urinary tract function (urinating). One feasible physiological therapy is pelvic floor muscle training. This can strengthen the muscles around the reproductive organs and increase muscle tone. The aim of the research was to analyze differences in urinary tract function (mixi) in pregnant women before and after pelvic floor muscle training. This research method was carried out using a two-group pretest, posttest design. The research sample was pregnant women. A total of 60 people responded and activities were carried out for 6 days on 8-13 November 2022. Before and after PFME was carried out, urinary frequency and urine output were measured using a tool. The results showed that there was no difference in urinary frequency between the control and intervention groups (p = 0.664), and there was no difference in urine volume during urination between the control and intervention groups (p = 0.270). In the PFME intervention, there was no difference in urinary frequency between the control group and the intervention group (P = 0.566). There was a difference in urine volume when urinating between the control group and the intervention group (p=0.004). Therefore, to improve urinary tract function in pregnant women and thereby improve their quality of life, PFME should be included in the schedule to provide planned and daily physical activity and exercise. Keywords: Pregnancy, PFME, urinary tract (Miction)